2012
DOI: 10.1128/jb.00810-12
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Glycogen Metabolism in Chemolithoautotrophic Bacteria from Distinctive Kinetic and Regulatory Properties of ADP-Glucose Pyrophosphorylase from Nitrosomonas europaea

Abstract: bNitrosomonas europaea is a chemolithoautotroph that obtains energy by oxidizing ammonia in the presence of oxygen and fixes CO 2 via the Benson-Calvin cycle. Despite its environmental and evolutionary importance, very little is known about the regulation and metabolism of glycogen, a source of carbon and energy storage. Here, we cloned and heterologously expressed the genes coding for two major putative enzymes of the glycogen synthetic pathway in N. europaea, ADP-glucose pyrophosphorylase and glycogen syntha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The ADP-Glc PPase from R. jostii was characterized as a homotetrameric protein exhibiting similar S 0.5 values for substrates to those calculated for the enzyme from M. tuberculosis , but fivefold higher than those from the S. coelicolor enzyme, although with levels of activity in the same order of magnitude than the latter. Comparatively, the catalytic efficiency of the ADP-Glc PPase from R. jostii exhibits the lowest values with respect to homologous proteins from S. coelicolor and M. tuberculosis or even other PPases so far characterized ( Iglesias et al, 1991 ; Charng et al, 1992 ; Ballicora et al, 1995 , 2002 ; Ugalde et al, 1998 ; Uttaro et al, 1998 ; Gomez-Casati and Iglesias, 2002 ; Bosco et al, 2009 ; Asencion Diez et al, 2012 , 2013a , b , 2014 , 2015 ; Machtey et al, 2012 ; Ebrecht et al, 2015a , b ). Thus, the R. jostii ADP-Glc PPase might be an enzyme with low basal activity, as proposed for the ADP-Glc PPase from Streptococcus mutans with homotetrameric conformation (GlgC, with similar values of catalytic efficiency; Asencion Diez et al, 2013a ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The ADP-Glc PPase from R. jostii was characterized as a homotetrameric protein exhibiting similar S 0.5 values for substrates to those calculated for the enzyme from M. tuberculosis , but fivefold higher than those from the S. coelicolor enzyme, although with levels of activity in the same order of magnitude than the latter. Comparatively, the catalytic efficiency of the ADP-Glc PPase from R. jostii exhibits the lowest values with respect to homologous proteins from S. coelicolor and M. tuberculosis or even other PPases so far characterized ( Iglesias et al, 1991 ; Charng et al, 1992 ; Ballicora et al, 1995 , 2002 ; Ugalde et al, 1998 ; Uttaro et al, 1998 ; Gomez-Casati and Iglesias, 2002 ; Bosco et al, 2009 ; Asencion Diez et al, 2012 , 2013a , b , 2014 , 2015 ; Machtey et al, 2012 ; Ebrecht et al, 2015a , b ). Thus, the R. jostii ADP-Glc PPase might be an enzyme with low basal activity, as proposed for the ADP-Glc PPase from Streptococcus mutans with homotetrameric conformation (GlgC, with similar values of catalytic efficiency; Asencion Diez et al, 2013a ).…”
Section: Discussionmentioning
confidence: 90%
“…To the best of our knowledge, this is the first time that lack of substrate specificity toward NTPs is shown in an ADP-Glc PPase from bacteria ( Ballicora et al, 2003 ), including actinobacteria ( Asencion Diez et al, 2012 , 2015 ). The closest example is the enzyme from Nitrosomonas europaea , although the latter showed less than 10% activity with other NTPs and its activity with GTP was almost no detectable ( Machtey et al, 2012 ). Additionally, we report herein, for the first time, an unusual activity regarding the high preference for GlcN-1P.…”
Section: Discussionmentioning
confidence: 99%
“…8 and Table S1). A previous phylogenetic comparison between amino acid sequences of bacterial ADP-Glc PPases allowed differentiate a separate cluster including the enzyme from Grampositive bacteria with low G+C (Machtey et al, 2012).…”
Section: Fig 6 Sds-page (A) and Inmudetectionmentioning
confidence: 99%
“…Previous works reported that ADP-Glc PPase has a certain degree of promiscuity toward the substrates (Preiss et al, 1966 ; Lapp and Elbein, 1972 ; Hill et al, 1991 ; Machtey et al, 2012 ; Cereijo et al, 2016 ), but the control of this promiscuity has not been studied. Here, we analyzed the use of alternative substrates by the ADP-Glc PPase from Escherichia coli , and how the activators, fructose-1,6-bisphosphate (Fru-1,6-bisP) and pyruvate (Pyr), play a key role in substrate selection.…”
Section: Introductionmentioning
confidence: 99%